Improving industry 4.0 through service science: a framework to the portuguese ornamental stone sector in BIM procurement contex - Silva, Agostinho Manuel Antunes da (2018)
This thesis aims an exploratory evaluation of the Industry 4.0 (I4.0) impact on Portuguese Ornamental Stone (OS) firms’ response to the Threats resulting from the Building Information Modelling (BIM) procurement. The transition witnessed from the Third to the Fourth Industrial Age leads to the emergence of paradigms such as BIM, seeking efficiency in Architecture, Engineering and Construction (AEC) through a global approach and procurement oriented towards standardisable products and I4.0, where production comes to be supported by Cyber-Physical Systems (CPS). Integrated in the AEC supply chain, the OS sector shows Portugal to be the eighth country in OS trade worldwide, and the second per capita, with its competitiveness based on the products customization. BIM represents threats for its sustainability, particularly in firms of the Cluster Portugal Mineral Resources (CPMR). The literature review showed that Service Science (S-S) is an inter-disciplinary scientific field that combines Organisation with Tchnological Knowledge, with a view to categorizing, innovating and creating value for Service-Systems. Guided by the pragmatic paradigm and using the mixed methodology of parallel convergence, this research focuses on conceptualization of a Service Science Framework (Inovstone4.0), to which was applied a representative sample of CPMR companies. This Framework has allowed to measure the evolution of Key Concern Indicators (KCI) indexed to stakeholders’ concerns, when operations shifts from the current best practices to I4.0 operattions. From the results, it has been found significant relief of stakeholder’s concerns, regarding the time to deliver, costs, footprint and products conformity, when in BIM procurement context, the production evolves to I4.0, allowing to conclude that in technical terms, the impact of I4.0 on the threats arising from BIM procurement in CPMR tends to be positive; RESUMO: DESENVOLVIMENTO DA INDÚSTRIA 4.0 PELA SERVICE SCIENCE Modelo para a aumentar a Competitividade do Setor das Rochas Ornamentais Português em Contexto de Procurement BIM O objeto de estudo desta tese é explorar o potencial impacto da Industria 4.0 (I4.0) como resposta às ameaças resultantes da generalização do Building Information Modelling (BIM), nas empresas de Rochas Ornamentais (RO) portuguesas. Na transição da Terceira para a Quarta Era Industrial a que assistimos, emergem paradigmas como o BIM, que busca a eficiência na Arquitetura Engenharia e Construção (AEC) por via de uma abordagem global e de um modelo de procurement orientado para produtos standarizados e a I4.0, cuja produção passa a ser suportada por Cyber-Physical Systems (CPS). Integrado na cadeia de abastecimento da AEC, o setor das RO coloca Portugal como o oitavo país no comércio mundial de RO e segundo per capita, cuja competitividade provém da customização. Do procurement BIM, resultarão ameaças à sua sustentabilidade, nomeadamente nas empresas do Cluster Portugal Mineral Resources (CPMR). Da revisão de literatura verifica-se que a Service Science (S-S) é uma área científica interdisciplinar que combina organização e conhecimento tecnológico, com vista a categorizar, inovar e criar valor aos service-systems. Guiada pelo paradigma pragmatista e utilizando a metodologia mista paralela convergente, esta investigação centrou-se na conceptualização de um modelo S-S, que foi aplicado a uma amostra representativa das empresas do CPMR, permitiu medir de forma exploratória, a evolução das preocupações dos stakeholders, operacionalizadas por via de Key Concerns Indicators (KCI), quando as operações passam do estado atual, para o procurement BIM e produção I4.0. Dos resultados obtidos, verificou-se um alívio significativo das preocupações dos stakeholders quanto ao prazo de entrega, custo, sustentabilidade e qualidade dos produtos, quando as operações em contexto BIM evoluem para I4.0, permitindo concluir que em termos técnicos, o impacto da I4.0 sobre as ameaças resultantes do procurement BIM tende a ser positivo.